Тенденції розвитку інвестиційного ринку України в умовах економічної нестабільності - Stepanova, Daria; Stepanova, Inna (Dr. Viktor Koval, 2018)
Introduction. In recent years, Ukraine's economy is in a difficult situation, while maintaining its tendency to deteriorate. That is why investments in the creation of favorable conditions for its development play an important role. The attracted investments are the basis for the development of the Ukrainian economy, ensuring the possibility of its integration into the European socio-economic space, increasing the competitiveness of domestic enterprises, thereby reducing the level of dependence on imports and developing export potential. Aim and tasks. The purpose of the article is to conduct a comprehensive analysis of the current state of the Ukrainian investment market, identify key issues that impede the attraction of additional capital investments and the future prospects of investment in the economy of the country in accordance with current economic and political realities. Research results. The article reveals the role of investments in the further development of the Ukrainian economy. The complex analysis of the current state of the investment market of the country is carried out. In carrying out the analysis of the investment market, methods of statistical analysis, system generalization, qualitative and quantitative comparison were used. The main factors that negatively influence on this market are determined, restraining the development of investment activity and reducing the competitiveness of the Ukrainian economy. The main directions of increase of investment attractiveness, the realization of which will contribute to the growth of capital investments, are offered. Conclusion. On the basis of the analysis of the Ukrainian investment market, it was found that foreign investors are extremely cautious with the injection of additional flows into the Ukrainian economy. It is proved that this process is due to gaps in the economy and investment market of the country. At the same time, Ukraine belongs to countries with huge potential for attraction of investments due to the rich natural resources, scientific and technical potential, skilled labor, and favorable infrastructure. The key objectives of investment policy should be to implement a comprehensive solution to the country's economic, social and political problems. Effective reforms are needed to improve the situation in the country, which will stimulate business development, increase the living standards of the population and the economy of the country.